2017
DOI: 10.1051/0004-6361/201628771
|View full text |Cite
|
Sign up to set email alerts
|

Hα Doppler shifts in a tornado in the solar corona

Abstract: Context. High resolution movies in 193 Å from the Atmospheric Imaging Assembly (AIA) on the Solar Dynamic Observatory (SDO) show apparent rotation in the leg of a prominence observed during a coordinated campaign. Such structures are commonly referred to as tornadoes. Time-distance intensity diagrams of the AIA data show the existence of oscillations suggesting that the structure is rotating.Aims. The aim of this paper is to understand if the cool plasma at chromospheric temperatures inside the tornado is rota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…The prominence plasma is optically thick in Mg II h and k lines, while it is (approximately) optically thin in The Doppler pattern versus time in Mg II lines as well as in Hα evolves slowly during the 1 hour and half observation time with large cells changing from blue to red. This kind of evolution has been previously observed in a prominence-tornado (Schmieder et al 2017a).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The prominence plasma is optically thick in Mg II h and k lines, while it is (approximately) optically thin in The Doppler pattern versus time in Mg II lines as well as in Hα evolves slowly during the 1 hour and half observation time with large cells changing from blue to red. This kind of evolution has been previously observed in a prominence-tornado (Schmieder et al 2017a).…”
Section: Resultssupporting
confidence: 76%
“…In the South triangle (region B) a large redshift area is observed at 08:07 UT, the area is decreasing in size and is replaced by blueshift area at 08:38 UT. Such Dopplershift pattern has been observed in other prominences (Schmieder et al 2010(Schmieder et al , 2017a. Long sequences of Dopplershift observations of a prominence-tornado showed such an evolution.…”
Section: Hα Imaging Spectroscopysupporting
confidence: 72%
“…Both observations lasted for more than 2.5 hours, a duration that is long enough to identify possible periodic oscillation (alternation of red and blue shifts) with a ∼1-hour period as identified by Schmieder et al (2017). However, during the whole observations, these adjacent red and blue shifts appear to be persistent, and they do not show any sign change of the Doppler shift.…”
Section: Discussionmentioning
confidence: 92%
“…Using observations of two tornadoes with the Interface Region Imaging Spectrograph (IRIS, De Pontieu et al 2014), Levens et al (2016a) found no evidence of rotation through an analysis of the Mg ii k Doppler shift. More recently, Schmieder et al (2017) analyzed a solar tornado observed with Hα and found an alternation between redshifted and blueshifted regions, revealing a possible irregular periodicity of about 1 hour. Such behavior is not supposed to be caused by rotation.…”
Section: Introductionmentioning
confidence: 99%
“…[3] compared the defined features of solar corona at six locations along the track of the total solar ec-Open Access Natural Science lipse 2006; they found that the basic coronal structures were seen in the secured images, moreover, the observed features of solar corona on the processed image is agreement with other processed images from different locations. [4] used high-resolution movies in 193 Å from Atmospheric Imaging Assembly (AIA) on Solar Dynamic Observatory to show apparent rotation of a prominence observed during a coordinated. They found that the Doppler pattern observed in H-Alpha couldn't be interpreted as rotation of the cool plasma inside tornado.…”
Section: Introductionmentioning
confidence: 99%